2015
DOI: 10.1002/uog.14791
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cell‐free DNA in maternal blood in screening for fetal aneuploidies: updated meta‐analysis

Abstract: 18, 91.0% (95% CI, for trisomy 13, 90.3% (95% CI, for monosomy X and 93.0% (95% CI, for sex chromosome aneuploidies other than monosomy X. For twin pregnancies, the DR for trisomy 21 was 93.7% (95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
484
5
13

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 595 publications
(523 citation statements)
references
References 102 publications
(376 reference statements)
21
484
5
13
Order By: Relevance
“…Preliminary data have suggested that NIPT is a feasible test option for twin gestations8, 9, 10. Currently, due to the paucity of reported studies in twins, professional societies and others have called for more studies on NIPT performance in twin gestations11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary data have suggested that NIPT is a feasible test option for twin gestations8, 9, 10. Currently, due to the paucity of reported studies in twins, professional societies and others have called for more studies on NIPT performance in twin gestations11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Weighted pooled detection rates and falsepositive rates for trisomy 21, 18, 13, monosomy X and other sex aneuploidies are reported at 99.2% (0.09%), 96.3% (0.13%), 91% (0.13%), 90.3% (.23%) and 93% (0.14%) respectively. 4 This reflects a higher sensitivity, lower false positive rate and thus higher positive predictive values for trisomy 21 and 18 when compared with standard screening protocols. 5,6 The superior test performance characteristics, along with commercial marketing, have rapidly shifted the paradigm of prenatal screening in high-risk women and increased utilization is expected in low-risk women.…”
Section: Introductionmentioning
confidence: 99%
“…1 NIPT can be used from 10 weeks in pregnancy to screen for DS with high sensitivity (99.3%) and specificity (99.8%) and can detect other common chromosomal aneuploidies (Trisomy 18, Trisomy 13, and Monosomy X). 2,3 NIPT allows screening for these conditions with much greater specificity than traditional DS screening (DSS) 4 and thereby significantly reduces the need for invasive testing (chorionic villus sampling or amniocentesis) with the associated small miscarriage risk. 5 Following the first evidence in 2008 that NIPT for DS was feasible, 6,7 this test has moved swiftly into clinical practice with testing available in the private sector since 2011.…”
Section: Introductionmentioning
confidence: 99%